2018
DOI: 10.2355/isijinternational.isijint-2018-144
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Reaction Degradation for Three-dimensional Coke Pore Structure

Abstract: In order to investigate coke degradation behavior due to CO 2 gasification reaction in the blast furnace, mass transfer analyses with the reaction and stress analyses for coke considering its structure after the reaction were performed. Using the finite element method, CO 2 gas diffusion in a coke lump and consumption of coke matrices owing to the gasification reaction were considered for the coke model in which the actual coke structure was reproduced. The rate-controlling step was also evaluated calculating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Shohei MATSUO, 1) * Yasuhiro SAITO, 2) Yohsuke MATSUSHITA, 3) Hideyuki AOKI 3) and Hideyuki HAYASHIZAKI 3,4) distribution and thermal stress caused by the temperature gradient in the coke oven is necessary for the prediction of the formation of fissures during the carbonization of coke. Numerical analysis through models such as the finite element method (FEM) have been widely used to simulate the mechanical response of the coke, 6,[11][12][13] and for thermal stress analyses. 8,[14][15][16][17][18] Sato et al, 16) Goto et al 17) and Jenkins et al 8) performed the thermal stress analyses of coke models with major fissures using FEM and investigated the mechanism for the formation of fissures and factors that influence their spacing.…”
Section: Development Of Analytical Methods Of Predicting Fissures Formation For Carbonization Process Of Cokementioning
confidence: 99%
“…Shohei MATSUO, 1) * Yasuhiro SAITO, 2) Yohsuke MATSUSHITA, 3) Hideyuki AOKI 3) and Hideyuki HAYASHIZAKI 3,4) distribution and thermal stress caused by the temperature gradient in the coke oven is necessary for the prediction of the formation of fissures during the carbonization of coke. Numerical analysis through models such as the finite element method (FEM) have been widely used to simulate the mechanical response of the coke, 6,[11][12][13] and for thermal stress analyses. 8,[14][15][16][17][18] Sato et al, 16) Goto et al 17) and Jenkins et al 8) performed the thermal stress analyses of coke models with major fissures using FEM and investigated the mechanism for the formation of fissures and factors that influence their spacing.…”
Section: Development Of Analytical Methods Of Predicting Fissures Formation For Carbonization Process Of Cokementioning
confidence: 99%
“…This imaging method is mainly used for non-destructive observation of the internal structure of materials. Microfocus X-ray CT has been used to observe the pore structure of coke, to investigate the effect of pore structure on strength or reactivity of coke, [16][17][18] and to observe the carbonization process. 19) Microfocus X-ray CT provides a resolution of several microns.…”
Section: Three-dimensional Rapid Imaging and Shape Evaluation Of Mult...mentioning
confidence: 99%
“…However, it was believed that the gasification of Coke D also occurred in a reaction-controlled regime. Numazawa et al 22,23) investigated reaction mechanisms of coke degradation by CO 2 , and they found that the rate-determining step changed from reaction rate to gas diffusion at 1100 ºC. Ono et al 16) showed that pore structure inside a coke after CO 2 gasification at 1100 ºC was uniform.…”
Section: Hot Strength Of Lignite-cokementioning
confidence: 99%